2019
DOI: 10.1186/s12891-019-2628-7
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intraoperative periarticular injection in Total hip arthroplasty: a systematic review and meta-analysis

Abstract: Background Periarticular injection (PAI) is a regional analgesia method performed in total hip arthroplasty (THA) for postoperative pain relief. However, its efficacy and safety is still inconclusive. Therefore, we conducted this meta-analysis to assess the safety of PAI and to determine if PAI provides better pain relief and reduce the consumption of opioids after THA. Methods We searched PubMed, Web of Science, Embase and the Cochrane Library comprehensively. Only ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
(44 reference statements)
1
27
0
Order By: Relevance
“…Despite the different opioids used in the included studies, data were pooled together for a meta-analysis as they belonged to the same class of drugs. 38 Previous meta-analysis studies have also pooled different opioids for pain relief in a single meta-analysis. 39,40 On the pooling of data, we found significantly reduced pain with the use of intra-articular opioids at all time points.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the different opioids used in the included studies, data were pooled together for a meta-analysis as they belonged to the same class of drugs. 38 Previous meta-analysis studies have also pooled different opioids for pain relief in a single meta-analysis. 39,40 On the pooling of data, we found significantly reduced pain with the use of intra-articular opioids at all time points.…”
Section: Discussionmentioning
confidence: 99%
“…We followed the statement on preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines (Table 1) and searched a comprehensive search on databases including PubMed, Embase, the Cochrane Library and Web of Science from the earliest record to September 2019. The following searching strategy was similar to the article we have published before [15]. We reviewed all of the articles that discussed continuous femoral nerve block (cFNB) versus singleinjection femoral nerve block (sFNB) in TKA.…”
Section: Search Strategymentioning
confidence: 99%
“…It is worth mentioning that liposomal bupivacaine has been associated with more superior outcomes in patients undergoing THR compared to traditional bupivacaine [ 29 ]. Apart from that, a considerable number of studies have reported that LIA is associated with more sufficient postoperative analgesia and less opioid consumption [ 30 - 34 ]. Furthermore, another recent study has suggested that LIA not only represents an effective method of analgesia but it also leads to a reduced length of stay in the hospital [ 35 ].…”
Section: Reviewmentioning
confidence: 99%